Advanced Non-Unit Protection Strategy for MMC-HVDC Grids Leveraging Two-Dimensional High-Frequency Characteristics via HHT and SVM - Chenglin Ren; Yige Hu; Xiang Lu; Yue Chen; Kepeng Xia; Hailin Li (Energies)
The rapid development of direct current (DC) grids poses significant challenges to the speed, reliability, and selectivity of fault protection systems. These systems are required to identify and distinguish between internal and external faults despite the constraints of limited information and time. This study introduces a non-unit protection scheme based on the classification of two-dimensional feature parameters utilizing the Hilbert–Huang transform (HHT) and a support vector machine (SVM). Through time–frequency analysis of the voltage waveform following DC faults, critical information within the high-frequency component of the fault voltage, specifically, the instantaneous frequency and amplitude of the wavefront, is extracted to distinguish internal from external faults. Two-dimensional feature parameters are associated with signal attenuation and distortion during fault propagation via the transmission path, thereby providing a foundation for precise fault identification. The employment of an SVM ensures the selectivity of this scheme without relying on protection settings. The efficacy of the scheme is validated through simulations conducted using PSCAD/EMTDC across various fault scenarios.